Optimum storage depths for structural CO2 trapping - Iglauer, Stefan (Elsevier, 2018)
© 2018 Elsevier Ltd Structural trapping is the primary CO2geo-storage mechanism, and it has historically been quantified by CO2column heights, which can be permanently immobilized beneath a caprock, using a buoyancy force-capillary force balance. However, the high dependence of CO2-wettability (a key parameter in the above analysis) on pressure and temperature – and thus storage depth – has not been taken into account. Importantly, rock can be CO2-wet at high pressure, and this wettability reversal results in zero structural trapping below a certain storage depth (~2400 m maximum caprock depth for a most likely scenario is estimated here). Furthermore, more relevant than the CO2column height is the actual mass of CO2which can be stored by structural trapping (mCO2). This aspect has now been quantified here, and importantly, mCO2goes through a maximum at ~1300 m depth, thus there exists an optimal storage depth at around 1300 m depth.